2016
DOI: 10.1016/j.immuni.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Akt1 Kinase-Mediated Mitophagy Modulates Apoptosis Resistance and Pulmonary Fibrosis

Abstract: Summary Idiopathic pulmonary fibrosis (IPF) is a devastating lung disorder with increasing incidence. Mitochondrial oxidative stress in alveolar macrophages is directly linked to pulmonary fibrosis. Mitophagy, the selective engulfment of dysfunctional mitochondria by autophagasomes, is important for cellular homeostasis and can be induced by mitochondrial oxidative stress. Here, we show Akt1 induced macrophage mitochondrial reactive oxygen species (ROS) and mitophagy. Mice harboring a conditional deletion of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
355
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(375 citation statements)
references
References 54 publications
20
355
0
Order By: Relevance
“…Our findings are consistent with a recent publication demonstrating that macrophage-derived TGF-β contributes to fibrosis in WT mice and that macrophages from IPF patients exhibit increased TGF-β expression (40). While our data indicate that macrophage TGF-β promotes fibrosis through a major effect on the lung epithelium in HPS, additional roles for macrophage-derived TGF-β are likely, including activation and differentiation of fibroblasts (40).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with a recent publication demonstrating that macrophage-derived TGF-β contributes to fibrosis in WT mice and that macrophages from IPF patients exhibit increased TGF-β expression (40). While our data indicate that macrophage TGF-β promotes fibrosis through a major effect on the lung epithelium in HPS, additional roles for macrophage-derived TGF-β are likely, including activation and differentiation of fibroblasts (40).…”
Section: Discussionsupporting
confidence: 92%
“…For example, BAL macrophages from HPS patients produce excess levels of several cytokines and chemokines ex vivo (9), and our previously published data demonstrate that murine HPS macrophages are primed, exhibiting hyperresponsiveness to LPS, TLR2, and TLR3 agonists (8). Our findings are consistent with a recent publication demonstrating that macrophage-derived TGF-β contributes to fibrosis in WT mice and that macrophages from IPF patients exhibit increased TGF-β expression (40). While our data indicate that macrophage TGF-β promotes fibrosis through a major effect on the lung epithelium in HPS, additional roles for macrophage-derived TGF-β are likely, including activation and differentiation of fibroblasts (40).…”
Section: Discussionsupporting
confidence: 92%
“…However, in a different set of studies, mice deficient in Parkin were found to be resistant to bleomycin-induced lung fibrosis 195 .…”
Section: Targets and Therapeutic Interventions For Mitochondrial Damagementioning
confidence: 99%
“…The mechanism of antifibrotic effect by PINK1 may include prevention of cell death by preserving mitochondrial function of pulmonary epithelial cells (96,97). In addition, Parkinson protein 2 E3 ubiquitin protein ligase (PARK2), another key mitophagyassociated molecule, is also implicated in myofibroblast differentiation and proliferation (98), although function of PARK2 on lung fibrosis needs to be further investigated (98,99). It remains unclear whether the observed accumulation of dysfunctional mitochondria and defective mitophagy in the lung of patients with IPF is a consequence of IPF or cause of IPF.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%